2007
DOI: 10.1556/oh.2007.28010
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance results of nosocomial infections of the ICU in Kenézy Hospital, based on two years data

Abstract: Nosocomial surveillance is useful in detecting nosocomial infections in ICU. A multidisciplinary approach and partnership between the physicians and infection control nurses is needed. Patient-to-nurse ratio is an independent risk factor for nosocomial infections in intensive care, this must be kept in mind when planning rationalization of the number of nursing staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Although we did not ascertain this correlation as a part of this study, our previous studies corresponding to the UTIs described in patients aged ≥65 years of age, and in male patients (whom are affected by complicated UTIs, usually in advanced ages) have both shown higher rates of resistance to UTI-specific drugs (nitrofurantoin, fosfomycin), 3GCs, fluoroquinolones, and a higher prevalence of MDR isolates overall, compared to the general population [59,60]. The burden of UTIs in healthcare-associated infections has been highlighted by a nosocomial surveillance study in a ~1600-bed hospital in Eastern Hungary, where 21.1% of such infections were UTIs during the study period (2004)(2005)(2006) [61]. In addition, a study by Bánhidy et al reported that 5.7% of mothers were affected by UTIs during pregnancy, and these pregnancies had a higher proportion of preterm births (10.4% vs. 9.1%) [62].…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not ascertain this correlation as a part of this study, our previous studies corresponding to the UTIs described in patients aged ≥65 years of age, and in male patients (whom are affected by complicated UTIs, usually in advanced ages) have both shown higher rates of resistance to UTI-specific drugs (nitrofurantoin, fosfomycin), 3GCs, fluoroquinolones, and a higher prevalence of MDR isolates overall, compared to the general population [59,60]. The burden of UTIs in healthcare-associated infections has been highlighted by a nosocomial surveillance study in a ~1600-bed hospital in Eastern Hungary, where 21.1% of such infections were UTIs during the study period (2004)(2005)(2006) [61]. In addition, a study by Bánhidy et al reported that 5.7% of mothers were affected by UTIs during pregnancy, and these pregnancies had a higher proportion of preterm births (10.4% vs. 9.1%) [62].…”
Section: Discussionmentioning
confidence: 99%
“…Disinfection is divided into disinfection of a high, medium and low level (Friedman, Newsom, 2007). Disinfection of the surfaces is one of the most important hygienic procedures in a hospital on which safety of patients and the medical stuff depends (Orosi et al, 2007). The aim of constant cleaning and disinfection of the premises is to put a stop to the spread of the agents of a disease in examining, treating and nursing the patient (Lithuanian hygiene norm HN 47-1:2010HN 47-1: , 2010Eckstein et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…According to a recent report by Orosi, the most common kind of nosocomial bacteremia is relating to respiratory tract infection not blood stream infection. [ 2 ] To manage CRBSI is very important. Good prevention and control program for this problem must be implemented in each hospital.…”
mentioning
confidence: 99%